A Novel Random Split Point Procedure Using Extremely Randomized (Extra) Trees Ensemble Method for Human Activity Recognition - Padmaja, B; Prasa, V V Rama; Sunitha, K V N (EAI Endorsed Transactions on Pervasive Health and Technology, 2020)
INTRODUCTION: Automatic detection and recognition of various human physical movements while performing daily life activities such as walking, jogging, running, sitting, standing etc. are usually considered as Activity Recognition (AR). AR is a prominent research area in many applications, such as elderly care, security and surveillance, smart homes, health and fitness. Extremely Randomized Trees Classifier (ET Classifier) is a type of ensemble learning technique used in Activity Recognition, which clusters several different decision trees into a forest from a single learning set and gives the classification result. But it suffers from high variance and over-fitting problem due to high inter-dependency among hyperparameters during model building. OBJECTIVES: The primary objective of this paper is to propose a novel RandomSplitPoint procedure for Extra tree classifier to make the existing approach more robust, less variance, less computational time in obtaining optimal split points and faster in model building. This approach generates K random split points from all the candidate features of the dataset and selects the best split point based on the maximum score obtained by information gain measure. METHODS: In the proposed method to improve the randomization and accuracy of AR system, a novel random split-point procedure for ET classifier is proposed. This approach reduces the bias-variance problem induced due to the three hyperparameters such as K, nmin and M used in split-point procedure of existing ET classifier (K : number of randomly selected attributes at each node, nmin : minimum sample size for splitting a node, M : number of decision trees for ensemble). This approach generates K random split points from all the candidate features of the dataset and selects the best split point based on the maximum score obtained by information gain measure. RESULTS: The proposed approach is experimented with two public AR datasets HAR and HAPT (UCI Machine Learning Repository) containing 6 and 12 activities respectively. In HAR dataset, smartphone sensed sensor signals of 3 static and 3 dynamic human daily activities are there, where as in HAPT dataset apart from these 6 daily activities, 6 postural transitions data is available. Experimental results and comparative analysis show that the proposed method outperforms over other existing techniques with an accuracy of 94.16% for HAR dataset and 92.63% for HAPT dataset. It also takes less computational time in finding optimal split-points and less model building time. CONCLUSION: AR systems can be used as an intelligent system in healthcare to monitor the behaviour of healthy people by recognizing their daily activities. These systems also help in early detection of some chronic diseases and improve the quality of life. In this paper, an attempt is made to improve the accuracy of Activity Recognition over some existing methods.